Dual pH and thermoresponsive alternating polyampholytes in alcohol/water solvent mixtures. Issue 12 (26th February 2020) - Maji, Samarendra; Jerca, Valentin Victor; Hoogenboom, Richard
Abstract : Polyampholytes consist of alternating opposite charges were synthesized by alternating RAFT (co)polymerization of cationic and anionic monomers and their pH dependent thermoresponsive behavior in water and alcohol/water solvent mixtures is reported. Abstract : Synthesis of polyampholytes based on cationic and anionic monomers that exhibit upper critical solution temperature (UCST) behavior is challenging as both the monomers need to be incorporated in stoichiometric amounts. By virtue of their charges, these polymers can exhibit special properties when both their ratios and/or the distance between the two charges are tuned. Here, the synthesis of alternating charge-neutral polyampholytes is described via reversible addition–fragmentation chain transfer (RAFT) statistical copolymerization of cationic styrenic and anionic N -substituted maleimide monomers. The percentage of N, N -dimethylaminomethylstyrene (DMAMSt) and N -carboxyethylmaleimide (CEMI) monomers in P(DMAMSt- alt -CEMI) copolymers is in 50/50 molar ratios, as confirmed by 1 H NMR measurements during the polymerization of DMAMSt and t BuEMI monomers. The thermoresponsive UCST behavior of the obtained charge neutral polyampholytes is demonstrated in water and alcohol–water (methanol, ethanol and 2-propanol) solvent mixtures. Moreover, the effect of the charge neutral polyampholyte concentration on the UCST phase transition in ethanol/H2 O solvent mixtures is discussed. The intermediate tert -butyl protected CEMI-based alternating copolymers P(DMAMSt- alt-t BuEMI) were found to be pH responsive and a diblock copolymer with a poly( N, N -isopropylacrylamide) block (PNIPAM- b -P(DMAMSt- alt-t BuEMI) demonstrated pH and LCST thermoresponsive behavior. These results demonstrate the use of these dual responsive polymers for future work on the exploration of these cationic and thermoresponsive polymers for the development of self-assembled responsive drug carriers.